Sodium ion solid electrolyte system, battery and preparation method of sodium ion solid electrolyte system

By combining inorganic and organic materials in sodium batteries, and adding gel electrolytes to the battery liquid, the problems of low ion conductivity and poor interface contact are solved, and the comprehensive performance and safety of sodium solid-state batteries are improved.

CN119890417AActive Publication Date: 2025-04-25XIAOGAN CORNEX NEW ENERGY INNOVATION TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510058074.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The solid electrolytes of existing sodium batteries have low ion conductivity and poor interface contact, which poses safety hazards.

Method used

Combination of inorganic and organic materials is used to prepare composite solid electrolyte membranes, plasticizers are added to improve ion transfer rate and improve SEI interface, and gel electrolyte is added during injection to improve interface contact.

Benefits of technology

It improves the ionic conductivity and safety performance of sodium solid-state batteries, reduces the amount of liquid injection of the battery, and enhances the cycle stability and capacity of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005242013570000131
    Figure BDA0005242013570000131
  • Figure BDA0005242013570000141
    Figure BDA0005242013570000141
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium ion batteries, and particularly relates to a sodium ion solid electrolyte system, a battery and a preparation method thereof.The solid electrolyte system comprises a solid electrolyte membrane and a gel electrolyte formed by curing a gel electrolyte precursor solution, and the solid electrolyte membrane is prepared from a polymer matrix and an inorganic solid electrolyte, sodium salt, a plasticizer and a first solvent; the inorganic solid electrolyte comprises an oxide electrolyte; the gel electrolyte precursor solution is prepared from the following raw materials: a monomer, sodium salt, an auxiliary agent, an initiator and a second solvent; the auxiliary agent is prepared from one or more than two of ethoxypentafluorocyclotriphosphazene, hexafluorocyclotriphosphazene, pentafluorophenoxy cyclotriphosphazene, triethyl phosphate and trimethyl phosphate. The solid electrolyte membrane disclosed by the invention has relatively high ionic conductivity and dendritic crystal resistance, and the gel electrolyte can improve the interface problem of the sodium-ion solid-state battery and reduce the liquid injection amount of the battery, so that the safety performance of the sodium-ion solid-state battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of sodium ion batteries, and in particular relates to a sodium ion solid electrolyte system, a battery and a preparation method thereof. Background Art

[0002] As the world faces the problems of energy depletion and environmental pollution, renewable clean energy is the goal that people will pursue in the future. In recent years, the rapid development and widespread application of lithium-ion batteries have led to the rapid consumption of lithium. At the same time, the scarcity of lithium resources (the lithium content in the earth's crust is about 0.065wt%) has caused the cost of the corresponding batteries to double. Therefore, researchers will use the abundant sodium (the sodium content in the earth's crust is about 2.75wt%) to make a new type of battery - sodium battery. The abundant sodium resources on the earth and the low cost have attracted more and more attention to sodium batteries.

[0003] However, most of the current research on sodium batteries is based on liquid electrolytes, which are flammable, volatile and leaky, causing sodium batteries to have safety issues that cannot be ignored. The use of flame-retardant, non-volatile, and leak-free solid electrolytes can effectively improve safety, but the solid electrolytes have low ionic conductivity and large interface impedance. Therefore, the development of high-safety, high-energy-density solid-state sodium batteries is quite challenging and meaningful. "Organic-inorganic" composite solid electrolytes have the advantages of both polymer solid electrolytes and inorganic solid electrolytes, which can improve the ionic conductivity of solid electrolytes and improve the safety performance of batteries to a certain extent. However, composite solid electrolytes still have the problem of poor interface contact. In view of this, the present invention is specially proposed. Summary of the invention

[0004] In order to solve the deficiencies and shortcomings of existing sodium batteries, the present invention provides a sodium ion solid electrolyte system, a battery and a preparation method thereof. The sodium ion solid electrolyte system includes a solid electrolyte membrane and a gel electrolyte. First, a thin composite solid electrolyte membrane is prepared by combining inorganic and organic materials. The electrolyte membrane has excellent electrochemical properties, high ionic conductivity and anti-dendritic effect, and the plasticizer therein has good sodium salt solubility and electrochemical stability, which helps to improve the ion transfer rate and improve the SEI interface. After being applied to sodium ion batteries, the safety performance of the battery can be improved. Then, a small amount of gel electrolyte is added when the solid electrolyte membrane is injected into the sodium ion solid battery to avoid the risk of leakage in the battery, greatly improve the contact interface between the electrolyte membrane and the positive and negative electrodes, which is beneficial to the battery capacity and cycle stability, and the additive in the gel has a flame retardant effect, which further improves the safety performance of the sodium ion solid battery. The sodium ion solid electrolyte system of the present invention solves the problems of low ionic conductivity and poor interface contact of the solid electrolyte, can improve the comprehensive performance of the sodium solid-state battery, and has a simple process, and is expected to be mass-produced in large-scale industrialization.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] In a first aspect, a sodium ion solid electrolyte system comprises a solid electrolyte membrane and a gel electrolyte formed by solidifying a gel electrolyte precursor solution, wherein the raw materials for preparing the solid electrolyte membrane comprise: a polymer matrix, an inorganic solid electrolyte, a sodium salt, a plasticizer, and a first solvent; the inorganic solid electrolyte comprises one or more of a NASICON-type structured oxide electrolyte, a perovskite-type structured oxide electrolyte, and an antiperovskite-type structured oxide electrolyte;

[0007] The raw materials for preparing the gel electrolyte precursor solution include: monomers, sodium salt, auxiliary agents, initiators, and a second solvent; the auxiliary agents include one or more of ethoxy pentafluorocyclotriphosphazene, hexafluorocyclotriphosphazene, pentafluorophenoxycyclotriphosphazene, triethyl phosphate, and trimethyl phosphate.

[0008] Furthermore, the thickness of the solid electrolyte membrane is 5 to 100 μm;

[0009] And / or, in a solid electrolyte membrane, the raw materials for preparing the solid electrolyte membrane include the following components by weight: 5 to 15 parts of a polymer matrix, 2 to 6 parts of an inorganic solid electrolyte, 2 to 5 parts of a sodium salt, 0.5 to 1.5 parts of a plasticizer, and 50 to 100 parts of a first solvent;

[0010] And / or, in the gel electrolyte, the raw materials for preparing the gel electrolyte precursor solution include the following components by mass: 5-15 parts of monomer, 10-30 parts of sodium salt, 2.5-7.5 parts of auxiliary agent, 0.1-0.3 parts of initiator, and 50-100 parts of second solvent.

[0011] Furthermore, in the raw materials for preparing the solid electrolyte membrane, the plasticizer includes one or more of imidazole ionic liquids, piperidine ionic liquids, pyrrole ionic liquids, quaternary ammonium ionic liquids, amide ionic liquids, succinonitrile or glutaronitrile;

[0012] And / or, the polymer matrix includes one or more of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyvinyl carbonate, polymethyl methacrylate, and polyvinyl pyrrolidone;

[0013] And / or, the particle size of the inorganic solid electrolyte is 0.1 to 10 μm;

[0014] And / or, the first solvent includes one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-diethylformamide, acetonitrile, and acetone.

[0015] Furthermore, in the raw materials for preparing the gel electrolyte precursor solution, the initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate;

[0016] And / or, the second solvent includes one or more of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl formate, methyl acetate, fluoroethylene carbonate, methyl propionate, ethyl propionate, ethyl acetate, γ-butyrolactone, tetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxypropane, triethylene glycol dimethyl ether, dimethyl sulfoxide, dimethyl ether, vinyl sulfite, propylene sulfite, dimethyl sulfite or diethyl sulfite.

[0017] Furthermore, in the raw materials for preparing the gel electrolyte precursor solution, the monomers include one or more of polyacrylate monomers and polyether monomers.

[0018] Furthermore, the average molecular weight of the polyacrylate monomer is 400-2000.

[0019] Furthermore, in the raw materials for preparing the solid electrolyte membrane and / or the raw materials for preparing the gel electrolyte precursor solution, the sodium salt includes one or more of sodium hexafluorophosphate, sodium fluoride, sodium difluorooxalatoborate, sodium borate, sodium silicate, sodium oxalate, sodium acetate, sodium hexafluoroarsenate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluorosulfonyl)imide.

[0020] In a second aspect, a sodium ion solid-state battery comprises the sodium ion solid-state electrolyte system described in the first aspect.

[0021] In a third aspect, a method for preparing the sodium ion solid-state battery according to the second aspect comprises the following steps:

[0022] (1) dissolving a polymer matrix in a first solvent, adding a sodium salt, a plasticizer, and an inorganic solid electrolyte, and stirring and dispersing the mixture to form a mixed liquid;

[0023] (2) applying the mixed solution on a substrate by scraping, and heating to volatilize the first solvent to obtain a solid electrolyte membrane;

[0024] (3) dispersing the monomer in the second solvent, then adding the sodium salt, the auxiliary agent, and the initiator, and stirring evenly to form a gel electrolyte precursor solution;

[0025] (4) Assembling a sodium ion battery using a positive electrode, a negative electrode and a solid electrolyte membrane, injecting a gel electrolyte precursor into the battery, and heating to solidify it, thereby obtaining a sodium ion solid-state battery.

[0026] Further, the substrate is a polytetrafluoroethylene plate, a glass plate or a PET plate;

[0027] And / or, the volatilization method of the first solvent includes: placing the substrate coated with the mixed solution under vacuum drying at 60 to 90° C. for 8 to 24 hours;

[0028] and / or, the injection volume of the gel electrolyte precursor solution is 5 to 15 μL;

[0029] And / or, the curing temperature is 60-90° C. and the curing time is 2-4 hours.

[0030] Compared with the prior art, the present invention has at least the following beneficial effects:

[0031] 1) The solid electrolyte system of the present invention comprises a solid electrolyte membrane and a gel electrolyte, wherein the solid electrolyte membrane has high ionic conductivity and anti-dendrite effect, and the gel electrolyte can improve the interface problem of the sodium ion solid-state battery and reduce the injection amount of the battery, thereby improving the safety performance of the sodium solid-state battery.

[0032] In the present invention, the solid electrolyte membrane is composed of an organic-inorganic solid electrolyte, and the polymer matrix can ensure that the electrolyte membrane has a certain mechanical strength. The inorganic solid electrolyte provides an additional sodium ion migration path while reducing the crystallinity of the polymer, thereby improving the ionic conductivity of the electrolyte membrane. The plasticizer has good sodium salt solubility and electrochemical stability, which helps to improve the ion transfer rate and improve the SEI interface. When the solid electrolyte membrane is applied to a sodium ion battery, a small amount of gel electrolyte precursor is added during the injection process to replace the conventional sodium ion battery electrolyte. Through the action of the initiator, the solidified gel electrolyte is heated to avoid the risk of leakage in the battery, and the interface impedance can be reduced and the cycle performance can be improved. In addition, due to the addition of additives in the gel electrolyte, the safety of the sodium ion solid-state battery is further improved.

[0033] 2) The preparation method of the present invention adopts an "organic-inorganic" composite method to prepare a solid electrolyte membrane, which can combine the advantages of polymer electrolytes and inorganic solid electrolytes, improve the ionic conductivity of the electrolyte membrane while taking into account good mechanical properties, which helps to improve safety performance. The solid electrolyte membrane can meet the needs of both electrochemical properties and mechanical properties.

[0034] During the assembly of sodium-ion solid-state batteries, a small amount of gel electrolyte is added to improve the solid-solid contact interface, which is beneficial to the battery's capacity. At the same time, the gel electrolyte improves the safety performance of the battery compared to liquid electrolytes.

[0035] The solid electrolyte membrane prepared by the present invention is easy to operate and has a fast process, and can be used with current lithium battery equipment. The process of assembling sodium solid soft-pack batteries is simple and suitable for industrial production. DETAILED DESCRIPTION

[0036] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0037] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0038] The embodiment of the present invention provides a sodium ion solid electrolyte system with high comprehensive performance, including a solid electrolyte membrane and a gel electrolyte formed by curing a gel electrolyte precursor liquid. The raw materials for preparing the solid electrolyte membrane include a polymer matrix, an inorganic solid electrolyte, a sodium salt, a plasticizer, and a first solvent; the inorganic solid electrolyte includes one or more of a NASICON-type structured oxide electrolyte, a perovskite-type structured oxide electrolyte, and an anti-perovskite-type structured oxide electrolyte; the raw materials for preparing the gel electrolyte precursor liquid include a monomer, a sodium salt, an auxiliary agent, an initiator, and a second solvent; the auxiliary agent includes one or more of ethoxy pentafluorocyclotriphosphazene, hexafluorocyclotriphosphazene, pentafluorophenoxycyclotriphosphazene, triethyl phosphate, and trimethyl phosphate.

[0039] In the solid electrolyte system of the present invention, the solid electrolyte membrane has high ionic conductivity and anti-dendrite effect, and the gel electrolyte can improve the interface problem of the sodium ion solid-state battery and reduce the injection amount of the battery, thereby improving the safety performance of the sodium solid-state battery.

[0040] In the present invention, the solid electrolyte membrane is composed of an organic-inorganic solid electrolyte, the polymer matrix can ensure that the electrolyte membrane has a certain mechanical strength, and the inorganic solid electrolyte provides an additional sodium ion migration path while reducing the crystallinity of the polymer, thereby improving the ionic conductivity of the electrolyte membrane. The plasticizer has good sodium salt solubility and electrochemical stability, which helps to improve the ion transfer rate and improve the SEI interface. The solid electrolyte membrane provided by the embodiment of the present invention, when applied to a sodium ion battery, adds a small amount of gel electrolyte precursor solution instead of a conventional sodium ion battery electrolyte during the injection process, and through the action of the initiator, heats to form a solidified gel electrolyte, avoiding the risk of battery leakage, and can reduce the interface impedance and improve the cycle performance. In addition, due to the addition of additives in the gel electrolyte, the safety of the sodium ion solid-state battery is further improved. Among the additives, ethoxy pentafluorocyclotriphosphazene (PFPN), hexafluorocyclotriphosphazene (FPPN), pentafluorophenoxycyclotriphosphazene (HFPN) are fluorine-containing flame retardant additives, triethyl phosphate (TEP), trimethyl phosphate (TMP) are phosphorus-containing flame retardant additives, and the flame retardant mechanisms of the two are different. In terms of flame retardant effect, phosphorus-containing flame retardant additives are more effective, but their electrochemical performance is not as good as that of fluorine-containing flame retardant additives. Therefore, fluorine-containing flame retardant additives are more preferred in terms of electrochemical performance.

[0041] In some embodiments, in a solid electrolyte membrane, the raw materials for preparing the solid electrolyte membrane include the following components in parts by mass: 5 to 15 parts (such as 6 parts, 8 parts, 10 parts, 12 parts, 14 parts) of a polymer matrix, 2 to 6 parts (such as 6 parts, 8 parts, 10 parts, 12 parts, 14 parts) of an inorganic solid electrolyte, 2 to 5 parts (such as 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts) of a sodium salt, 0.5 to 1.5 parts (such as 0.6 parts, 0.8 parts, 1 parts, 1.2 parts, 1.4 parts) of a plasticizer, and 50 to 100 parts (such as 60 parts, 70 parts, 80 parts, 90 parts) of a first solvent.

[0042] In some embodiments, in a gel electrolyte, the raw materials for preparing the gel electrolyte precursor solution include the following components in parts by mass: 5 to 15 parts (such as 6 parts, 8 parts, 10 parts, 12 parts, and 14 parts) of a monomer, 10 to 30 parts (such as 13 parts, 16 parts, 19 parts, 22 parts, 25 parts, and 27 parts) of a sodium salt, 2.5 to 7.5 parts (such as 2.7 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 5.5 parts, 6 parts, 6.5 parts, and 7 parts) of an auxiliary agent, 0.1 to 0.3 parts (such as 0.13 parts, 0.16 parts, 0.19 parts, 0.22 parts, 0.25 parts, 0.27 parts, and 0.29 parts) of an initiator, and 50 to 100 parts (such as 60 parts, 70 parts, 80 parts, and 90 parts) of a second solvent.

[0043] In the present invention, the mass fractions of the raw materials for preparing the solid electrolyte membrane and the mass fractions of the raw materials for preparing the gel electrolyte precursor solution can be the same or different, but both satisfy their own ingredient ratios, such as the mass ratio of the polymer matrix, inorganic solid electrolyte, sodium salt, plasticizer, and first solvent in the solid electrolyte membrane is 5-15: 2-6: 2-5: 0.55-1.5: 50-100, and the mass ratio of the monomer, sodium salt, auxiliary agent, initiator, and second solvent in the gel electrolyte precursor solution is 5-15: 10-30: 2.5-7.5: 0.1-0.3: 50-100.

[0044] In some embodiments, the polymer matrix includes one or more of polyethylene oxide (PEO), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyacrylonitrile (PAN), polyvinyl carbonate (PPC), polymethyl methacrylate (PMMA), and polyvinyl pyrrolidone (PVP).

[0045] In some embodiments, the NASICON-type structured oxide electrolyte comprises: Na3Zr2Si2PO 12 、Na 3.1 Zr 1.95 Mg 0.05 Si2PO 12 ; Perovskite-type oxide electrolytes include: Na 0.5 La 0.5 ZrO3、Na 0.33 La 0.46 Zr 0.7 Nb 0.3 O3; Antiperovskite structure oxide electrolytes include: Na3OBH4, Na4OI2.

[0046] In some embodiments, the sodium salt includes one or more of sodium hexafluorophosphate, sodium fluoride, sodium difluorooxalatoborate, sodium borate, sodium silicate, sodium oxalate, sodium acetate, sodium hexafluoroarsenate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluorosulfonyl)imide.

[0047] In the sodium ion solid electrolyte system of the present invention, the sodium salts used in the solid electrolyte membrane and the gel electrolyte are optional and may be of the same type or different types.

[0048] In some embodiments, the plasticizer includes one or more of imidazole ionic liquids, piperidine ionic liquids, pyrrole ionic liquids, quaternary ammonium ionic liquids, amide ionic liquids, succinonitrile or glutaronitrile.

[0049] In some embodiments, the first solvent includes one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-diethylformamide, acetonitrile, and acetone.

[0050] In some embodiments, the monomer includes one or more of a polyacrylate monomer and a polyether monomer. Examples of the polyacrylate monomer include polytrimethylolpropane triacrylate (ETPTA) and polyethylene glycol dimethacrylate (PEGDA); examples of the polyether monomer include polyethylene glycol monomethyl ether and allyl polyoxyethylene ether. Preferably, the average molecular weight of the polyacrylate monomer is 400 to 2000 (such as 500, 700, 900, 1100, 1300, 1500, 1700, 1900), because the monomer is in liquid state when the molecular weight is low and becomes solid state when the molecular weight is high. Exceeding the range will increase the viscosity of the gel electrolyte, thereby reducing the electrochemical performance of the battery.

[0051] In some embodiments, the initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate.

[0052] In some embodiments, the second solvent includes one or more of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl formate, methyl acetate, fluoroethylene carbonate, methyl propionate, ethyl propionate, ethyl acetate, γ-butyrolactone, tetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxypropane, triethylene glycol dimethyl ether, dimethyl sulfoxide, dimethyl ether, ethylene sulfite, propylene sulfite, dimethyl sulfite or diethyl sulfite.

[0053] In some embodiments, the particle size of the inorganic solid electrolyte is 0.1 to 10 μm (eg, 0.2 μm, 0.5 μm, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm).

[0054] In some embodiments, the solid electrolyte membrane has a thickness of 5 to 100 μm (eg, 6 μm, 10 μm, 30 μm, 50 μm, 70 μm, 90 μm).

[0055] The technical scheme of the solid electrolyte system and the sodium ion solid-state battery preparation method in the present invention is:

[0056] A method for preparing a sodium ion solid electrolyte membrane and a solid-state battery comprises the following steps:

[0057] (1) dissolving a polymer matrix in a first solvent, adding a sodium salt, a plasticizer, and an inorganic solid electrolyte, and stirring and dispersing the mixture to form a mixed liquid;

[0058] (2) applying the mixed solution on a substrate by scraping, and heating to volatilize the first solvent to obtain a solid electrolyte membrane;

[0059] (3) dispersing the monomer in the second solvent, then adding the sodium salt, the auxiliary agent, and the initiator, and stirring evenly to form a gel electrolyte precursor solution;

[0060] (4) Assembling a sodium ion battery using a positive electrode, a negative electrode and a solid electrolyte membrane, injecting a gel electrolyte precursor into the battery, and heating to solidify it, thereby obtaining a sodium ion solid-state battery.

[0061] The preparation method of the sodium ion solid-state battery provided by the present invention is simple to operate and has efficient production. It is relatively consistent with the existing battery production route and does not require funds to purchase additional equipment. It can greatly promote the actual production and application of sodium solid-state batteries.

[0062] Optionally, the substrate is a polytetrafluoroethylene plate, a glass plate or a PET plate.

[0063] Optionally, the volatilization method of the first solvent includes: placing the substrate coated with the mixed solution at 60 to 90° C. and vacuum drying for 8 to 24 hours.

[0064] Optionally, the injection volume of the gel electrolyte precursor solution is 5 to 15 μL (such as 6 μL, 7 μL, 8 μL, 9 μL, 10 μL, 11 μL, 12 μL, 13 μL, 14 μL);

[0065] Optionally, the curing temperature is 60-90°C (eg, 65°C, 70°C, 75°C, 80°C, 85°C), and the curing time is 2-4h (eg, 2.5h, 3h, 3.5h).

[0066] The solid electrolyte membrane provided in the embodiment of the present invention is prepared by the preparation method provided in the embodiment of the present invention. The embodiments of the present invention will be described in detail below in conjunction with the examples. The following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If the specific conditions are not specified in the examples, they will be carried out under normal conditions. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased through normal channels.

[0067] Example 1

[0068] Preparation of solid electrolyte membrane

[0069] (1) Add 10g PVDF-HFP to 60g N-methylpyrrolidone (NMP) and stir at room temperature for more than 8h to form a uniform solution. Then add 3g sodium bis(fluorosulfonyl)imide (NaFSI) and 1g succinonitrile and stir for 2h to completely dissolve the sodium salt. Finally, add 4g inorganic solid electrolyte Na3Zr2Si2PO4 with a particle size of D50 = 700nm.12 The mixture was stirred overnight, during which ultrasonic dispersion was performed twice, each time for 15 min, to obtain a mixed solution.

[0070] (2) The mixed solution was scraped onto a polytetrafluoroethylene plate using a flat plate coater, with a scraper gap of 150 μm. The polytetrafluoroethylene plate coated with the slurry was transferred to a 70°C oven and vacuum dried for 12 hours to obtain a completely removable composite solid electrolyte membrane with a thickness of about 40 μm.

[0071] Preparation of gel electrolyte precursor

[0072] Add 1g of polyethylene glycol dimethacrylate (PEGDA) with a molecular weight of 600 to 4g of ethylene carbonate (EC) and 4g of propylene carbonate (PC) and mix well. Then add 2g of sodium hexafluorophosphate (NaPF6) and stir thoroughly to dissolve the sodium salt completely. Then add 0.5g of hexafluorocyclotriphosphazene (FPPN) and 20mg of initiator azobisisobutyronitrile (AIBN), stir for more than 1h, and finally obtain a gel electrolyte precursor solution.

[0073] Preparation of positive electrode

[0074] The positive electrode active material sodium vanadium phosphate (NVP), the conductive agent Super-P, and the binder PVDF were mixed in a mass ratio of 90:5:5, and a certain amount of NMP solvent was added and stirred to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on aluminum foil using a flat plate coating machine and dried at 110°C to obtain a positive electrode sheet with a surface density of about 5.0 mg / cm 2 .

[0075] Assembling sodium-ion solid-state batteries

[0076] The positive electrode sheet, solid electrolyte membrane, and metallic sodium are stacked in order, 5 μL of gel electrolyte precursor is added to both sides of the solid electrolyte membrane, and then packaged to obtain a button battery. The battery is left to stand at room temperature for 6 hours, and then placed in a 60°C oven for heating and curing for 2 hours to obtain a sodium ion solid-state battery.

[0077] Example 2

[0078] This embodiment is basically the same as Embodiment 1, except that:

[0079] When preparing the solid electrolyte membrane, 10 g of PVDF-HFP was replaced with 10 g of PVDF, and the rest were the same.

[0080] Example 3

[0081] This embodiment is basically the same as Embodiment 1, except that:

[0082] When preparing the solid electrolyte membrane, 10 g of PVDF-HFP was added to 60 g of N-methylpyrrolidone (NMP), instead of adding 10 g of PEO to 100 g of acetonitrile.

[0083] Example 4

[0084] This embodiment is basically the same as Embodiment 1, except that:

[0085] When preparing the solid electrolyte membrane, the inorganic solid electrolyte Na3Zr2Si2PO 12 Changing to perovskite electrolyte Na 0.5 La 0.5 ZrO3, particle size D50=800nm, the rest remain unchanged.

[0086] Example 5

[0087] This embodiment is basically the same as Embodiment 1, except that:

[0088] When preparing the gel electrolyte, 1 g of polytrimethylolpropane triacrylate (ETPTA) with a molecular weight of 428 was added to 4 g of ethylene carbonate (EC) and 4 g of propylene carbonate (PC) and mixed uniformly.

[0089] Example 6

[0090] This embodiment is basically the same as Embodiment 1, except that:

[0091] When preparing the gel electrolyte, sodium perchlorate (NaClO4) is used instead of sodium hexafluorophosphate, and the mixture is stirred thoroughly to completely dissolve the sodium salt.

[0092] Comparative Example 1

[0093] This comparative example is basically the same as Example 1, except that the inorganic solid electrolyte Na3Zr2Si2PO4 was not added during the preparation of the solid electrolyte membrane. 12 .

[0094] Comparative Example 2

[0095] This comparative example is basically the same as Example 1, except that no plasticizer succinonitrile is added during the preparation of the solid electrolyte membrane.

[0096] Comparative Example 3

[0097] This comparative example is substantially the same as Example 1, except that the auxiliary agent hexafluorocyclotriphosphazene is not added during the preparation of the gel electrolyte.

[0098] Comparative Example 4

[0099] This comparative example is basically the same as Example 1, except that the solid electrolyte membrane is replaced with a PE diaphragm when assembling the sodium ion solid-state battery, that is, only the gel electrolyte is used alone as the electrolyte (the gel film alone has poor strength as an electrolyte and cannot be used, so it is used together with a diaphragm).

[0100] Comparative Example 5

[0101] This comparative example is basically the same as Example 1, except that only the solid electrolyte membrane is used when assembling the sodium ion solid-state battery, and the gel electrolyte injection and formation are not performed, that is, only the solid electrolyte membrane is used alone as the electrolyte.

[0102] Experimental example

[0103] The electrochemical properties of the solid electrolyte membrane and the solid-state battery provided in each embodiment and comparative example were tested.

[0104] The test method is as follows:

[0105] (1) Ionic conductivity σ: A symmetrical button cell composed of stainless steel SS|solid electrolyte membrane|stainless steel SS was assembled, 10 μL of gel electrolyte was added, and the impedance spectrum was measured using an electrochemical workstation at 25 °C. The test frequency was 10 6 ~0.1Hz. The calculation formula of ionic conductivity is σ=L / (R*S). L is the thickness of the solid electrolyte membrane or the thickness of the diaphragm, R is the impedance, and S is the effective contact area.

[0106] (2) Capacity and long cycle test: Assemble button cells according to NVP | solid electrolyte membrane | sodium sheet, add 10 μL gel electrolyte, and perform capacity and cycle tests on the blue power test system with a cycle rate of 0.5C and a temperature of 25°C.

[0107] (3) Flammability test: disassemble the cured button cell, take out the solid electrolyte membrane or separator, and then ignite it to see whether it can burn;

[0108] (4) Mechanical properties test: The solid electrolyte membrane or the diaphragm prepared in the examples and comparative examples was used as a sample for testing. Each group of samples was cut into a strip test sample with a width of 20 mm and a length of 150 mm. The initial distance between the clamps of the electronic tensile machine was set to 100 mm. The two ends of the test sample along the length direction were placed in the upper and lower ends of the clamp in turn, and the clamp was clamped. During the test, the sample and the clamp were ensured to be in the same vertical direction without obvious tensile deformation. After the preparation was completed, the tensile test was carried out at a rate of 50 mm / min, and each group of samples was tested three times to obtain the average value.

[0109] Table 1 shows the electrochemical performance test results of various embodiments and comparative examples.

[0110]

[0111]

[0112] From Table 1, it can be seen that the solid electrolyte membrane prepared in the embodiment of the present invention and the assembled solid-state battery have excellent electrochemical properties, and the ionic conductivity is 4.5×10 -4 ~5.5×10 -4 S / cm, the first discharge capacity is 105-115mAh / g, the first efficiency is more than 90%, the 0.5C@200 cycle capacity retention rate is more than 95%, and the solid electrolyte membrane has good mechanical properties and is not flammable. In addition, the high cycle capacity retention rate of the battery also shows that the battery interface contact is good and the anti-dendrite effect is good.

[0113] Comparing Example 1 with Comparative Example 1, it can be seen that the addition of inorganic solid electrolyte has the effect of improving ion conductivity, and due to the addition of inorganic substances, the solid electrolyte membrane is not easy to burn.

[0114] Comparing Example 1 with Comparative Example 2, it can be seen that the addition of the plasticizer succinonitrile can dissociate more sodium salts, thereby improving the ionic conductivity of the solid electrolyte membrane, which is beneficial to the long-term cycle of the battery.

[0115] Comparing Example 1 with Comparative Example 3, it can be seen that the auxiliary agent hexafluorocyclotriphosphazene has a flame retardant effect and can improve the safety performance of the sodium ion solid electrolyte.

[0116] Comparing Example 1 with Comparative Example 4, it can be seen that the solid electrolyte membrane prepared by the present invention has higher ion conductivity than the PE separator, and the assembled battery also has a longer cycle life.

[0117] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A sodium ion solid electrolyte system, characterized in that: A gel electrolyte formed by solidifying a solid electrolyte membrane and a gel electrolyte precursor solution, wherein the raw materials for preparing the solid electrolyte membrane include: a polymer matrix, an inorganic solid electrolyte, a sodium salt, a plasticizer, and a first solvent; the inorganic solid electrolyte includes one or more of a NASICON-type structured oxide electrolyte, a perovskite-type structured oxide electrolyte, and an antiperovskite-type structured oxide electrolyte; The raw materials for preparing the gel electrolyte precursor solution include: monomers, sodium salt, auxiliary agents, initiators, and a second solvent; the auxiliary agents include one or more of ethoxy pentafluorocyclotriphosphazene, hexafluorocyclotriphosphazene, pentafluorophenoxycyclotriphosphazene, triethyl phosphate, and trimethyl phosphate.

2. The sodium ion solid electrolyte system according to claim 1, characterized in that: The thickness of the solid electrolyte membrane is 5 to 100 μm; And / or, in a solid electrolyte membrane, the raw materials for preparing the solid electrolyte membrane include the following components by weight: 5 to 15 parts of a polymer matrix, 2 to 6 parts of an inorganic solid electrolyte, 2 to 5 parts of a sodium salt, 0.5 to 1.5 parts of a plasticizer, and 50 to 100 parts of a first solvent; And / or, in the gel electrolyte, the raw materials for preparing the gel electrolyte precursor solution include the following components by mass: 5-15 parts of monomer, 10-30 parts of sodium salt, 2.5-7.5 parts of auxiliary agent, 0.1-0.3 parts of initiator, and 50-100 parts of second solvent.

3. The sodium ion solid electrolyte system according to claim 1, characterized in that: In the raw materials for preparing the solid electrolyte membrane, the plasticizer includes one or more of imidazole ionic liquids, piperidine ionic liquids, pyrrole ionic liquids, quaternary ammonium ionic liquids, amide ionic liquids, succinonitrile or glutaronitrile; And / or, the polymer matrix includes one or more of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylonitrile, polyvinyl carbonate, polymethyl methacrylate, and polyvinyl pyrrolidone; And / or, the particle size of the inorganic solid electrolyte is 0.1 to 10 μm; And / or, the first solvent includes one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylformamide, N,N-diethylformamide, acetonitrile, and acetone.

4. The sodium ion solid electrolyte system according to claim 1, characterized in that: In the raw materials for preparing the gel electrolyte precursor solution, the initiator includes one or more of azobisisobutyronitrile, azobisisovaleronitrile, azobisisoheptanenitrile, and dimethyl azobisisobutyrate; And / or, the second solvent includes one or more of propylene carbonate, ethylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, methyl formate, methyl acetate, fluoroethylene carbonate, methyl propionate, ethyl propionate, ethyl acetate, γ-butyrolactone, tetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxypropane, triethylene glycol dimethyl ether, dimethyl sulfoxide, dimethyl ether, vinyl sulfite, propylene sulfite, dimethyl sulfite or diethyl sulfite.

5. The sodium ion solid electrolyte system according to claim 1, characterized in that: In the raw materials for preparing the gel electrolyte precursor solution, the monomers include one or more of polyacrylate monomers and polyether monomers.

6. The sodium ion solid electrolyte system according to claim 5, characterized in that: The average molecular weight of the polyacrylate monomer is 400-2000.

7. The sodium ion solid electrolyte system according to claim 1, characterized in that: In the raw materials for preparing the solid electrolyte membrane and / or the raw materials for preparing the gel electrolyte precursor solution, the sodium salt includes one or more of sodium hexafluorophosphate, sodium fluoride, sodium difluorooxalatoborate, sodium borate, sodium silicate, sodium oxalate, sodium acetate, sodium hexafluoroarsenate, sodium tetrafluoroborate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, and sodium bis(trifluorosulfonyl)imide.

8. A sodium ion solid-state battery, characterized in that: Comprising the sodium ion solid electrolyte system as described in any one of claims 1-7.

9. A method for preparing a sodium ion solid-state battery as claimed in claim 8, characterized in that: The following steps are involved: (1) dissolving a polymer matrix in a first solvent, adding a sodium salt, a plasticizer, and an inorganic solid electrolyte, and stirring and dispersing the mixture to form a mixed liquid; (2) applying the mixed solution on a substrate by scraping, and heating to volatilize the first solvent to obtain a solid electrolyte membrane; (3) dispersing the monomer in the second solvent, then adding the sodium salt, the auxiliary agent, and the initiator, and stirring evenly to form a gel electrolyte precursor solution; (4) Assembling a sodium ion battery using a positive electrode, a negative electrode and a solid electrolyte membrane, injecting a gel electrolyte precursor into the battery, and heating to solidify it, thereby obtaining a sodium ion solid-state battery.

10. The preparation method according to claim 9, characterized in that: The substrate is a polytetrafluoroethylene plate, a glass plate or a PET plate; And / or, the volatilization method of the first solvent includes: placing the substrate coated with the mixed solution under vacuum drying at 60 to 90° C. for 8 to 24 hours; and / or, the injection volume of the gel electrolyte precursor solution is 5 to 15 μL; And / or, the curing temperature is 60-90° C. and the curing time is 2-4 hours.

Citation Information

Patent Citations

  • Sodium ion composite solid electrolyte and preparation method thereof

    CN113506910A

  • Gel polymer electrolyte with heterostructure and quasi-solid-state lithium metal battery

    CN114335708A

  • Gel electrolyte membrane and preparation method and application thereof

    CN115832417A

  • Gel electrolyte for sodium ion battery as well as preparation method and application of gel electrolyte

    CN116722214A

  • Gel electrolyte membrane and preparation method and application thereof

    CN117133971A

Cited By

  • Polymer electrolyte and preparation method and application thereof

    CN120824418A